Lipoprotein apheresis for the treatment of familial hypercholesterolemia. (October 2013) - Walji, Shahenaz; Neuwirth, Clare; Thompson, Gilbert R
Lipoprotein apheresis involves the extracorporeal removal of LDL and lipoprotein(a) particles from whole blood or plasma by adsorption, precipitation or differential filtration. Used repetitively, this provides a safe and effective means of treating patients at high risk of premature cardiovascular mortality and morbidity from genetically determined increases in these atherogenic lipoproteins that are refractory to conventional therapy. Although evidence of benefit is based mainly on nonrandomized data, the procedure is widely accepted as first-line therapy for homozygous familial hypercholesterolemia and is increasingly used to treat patients with cardiovascular disease due to statin-refractory heterozygous familial hypercholesterolemia or raised levels of lipoprotein(a). However, randomized clinical trial data are required before the last of these indications can be regarded as evidence based.